Transformational leadership and employee work quality in Nigerian Universities: The mediating role of teamwork effectiveness - Idris Adegboyega, Onikoyi; Arinloye, Felicia Omowumi (UIR Press, 2026)
Purpose: This study examines the structural relationship between transformational leadership and employee work quality in Nigerian Universities: The mediating role of teamwork effectiveness. Design/methodology/approach: A quantitative cross-sectional survey design was adopted. Stratified random sampling yielded 380 academic and non-academic staff respondents. Covariance-based structural equation modelling (CB-SEM) in IBM AMOS 23 was used to test the hypothesised relationships, supported by bias-corrected bootstrapping with 5,000 resamples. Findings: Transformational leadership did not exert a statistically significant direct effect on employee work quality through teamwork effectiveness. Teamwork effectiveness was the dominant direct predictor of work quality, and the structural pattern of results supports full mediation: the influence of transformational leadership on work quality is fully channelled through the collaborative team environment it constructs covariance. Limitations and Research implications: The cross-sectional design precludes causal inference, and the sample is restricted to Southwest Nigeria. Future research should employ longitudinal designs and extend sampling across multiple geopolitical zones and national contexts. Practical Implications: University administrators and policymakers should reorient performance improvement strategies from a narrow focus on individual leadership capacity to an integrated model that couples leadership development with deliberate team architecture, role clarity, and collaborative process design across academic and administrative units. Originality/value: This study provides the first CB-SEM-based test of teamwork effectiveness as a full mediator between transformational leadership and work quality in Nigerian universities. It contributes a methodologically rigorous Nigerian data point to the cross-regional literature and offers a documented demonstration of the consequences of model misspecification in CB-SEM.